Strategy for Beef Cattle Agribusiness Development in North Sulawesi - Jolyanis Lainawa; Paulus Kindangen; Tri Oldi Rotinsulu; J.F. Alfa Tumbuan (AIBPM Publisher, 2019)
The business of raising cattle in North Sulawesi is still carried out in traditionalextensive ways, because the main objective of farmers is to raise cattle only to be used as agricultural labor. As a result, the population and productivity of cattle in North Sulawesi are not well developed. Though the number of requests for beef consumption is very high, so that there is a gap between consumption needs and the availability of production. For the development of the agribusiness system, the concept of development strategy is needed, so the purpose of this study is to find a model for agribusiness development of beef cattle in North Sulawesi. The research method used is qualitative with a case study design. Data analysis is